A Review of Termite for Sustainable Green Building - Kusumawardhani, Dina Tiara; Almulqu, Aah Ahmad (Al-Hayat: Journal of Biology and Applied Biology, 2024)
Although 3106 termite species have been documented worldwide, little information is available on those in Indonesia. In this review, the Google Scholar search platform was used to obtain information on termite species. From the 34 reviewed sources, they were identified in 4 provinces across Indonesia. Among these sites, we found 106 termite species from the islands of Sumatera, Kalimantan, Sulawesi, and Java. The most predominant species in all regions were Macrotermes sp, Microtermes sp, and Coptotermes sp.